Risk of seizure recurrence in children with new-onset afebrile seizure (Medical Journal of Indonesia, 2023)
BACKGROUND A seizure is a brief change in the normal neuronal electrical activity of the brain that causes changes in consciousness, perception, behavior, or movement. This study aimed to evaluate clinical findings, initial electroencephalography (EEG), and brain imaging findings as predictors of seizure recurrence after the first nonfebrile seizure. METHODS This prospective follow-up study was conducted at Azadi Teaching Hospital, Kirkuk from July 2019 to January 2022 and enrolled 150 patients, ranging from 1 month to 15 years of age, who presented with their first afebrile seizure. The seizure types were classified based on the International League Against Epilepsy in 2017. A brain imaging with EEG was performed within 72 hours after admission. RESULTS The median age of the patients was 5 years. A higher risk of seizure recurrence occurred in patients with focal seizure (relative risk [RR] = 6.604) (95% confidence interval [CI] 3.975–10.971), seizure occurrence at sleep (RR = 3.815) (95% CI 2.410–6.039), an abnormal neurological presentation such as Todd’s paralysis (RR = 1.739) (95% CI 1.252–2.415), a positive family history of seizures (RR = 2.333) (95% CI 1.598–3.408), abnormal EEG (RR = 0.171) (95% CI 0.092–0.318), and abnormal brain image findings (RR = 0.681) (95% CI 0.492–0.941) within 72 hours. Seizure recurrence was not correlated with sex. CONCLUSIONS Early and late childhood new-onset afebrile seizures with a positive family history, focal epilepsy, seizure during sleep, prolonged attack duration with frequent attacks within 24 hours, and abnormal initial EEG and brain image had a high risk of seizure recurrence.